Are we ready for digital transformation? The role of organizational culture, leadership and competence in building digital advantage - Szymon Cyfert; Wojciech Dyduch; Witold Szumowski; Gunnar Prause (Central European Management Journal)
Purpose – The development of ITC technologies, the emergence of novel digital business models, the growing imperative for cybersecurity assurance and the phenomenon of digital disruption caused by unexpected crises force companies to rethink and redefine their strategies. Nevertheless, empirical evidence is not fully consistent with the prevailing opinion among management practitioners that technology is a crucial factor in ensuring the digital transformation’s effectiveness. The article identifies the reasons for the limited level of readiness of contemporary organizations for digital transformation, highlighting the role of the organization’s soft components. Design/methodology/approach – Addressing the complexity of digitizing phenomena, the article presents the role of organizational culture, digital leadership and digital competencies in organizational transformation processes. Findings – By emphasizing the significance of an organization’s soft components in the context of digital transformation, we suggest that while technological advancement constitutes a crucial aspect of this process, it is not the mere implementation of technological solutions that is paramount to its efficacy. The crux of the matter lies in the transformation of soft management factors, encompassing the provision of digital leadership, the cultivation of digital competencies and the establishment of a digital organizational culture. Originality/value – While digital transformation ultimately necessitates action in the area of infrastructure, the advantages of transformation will only be fully realized once an adequate level of maturity has been attained in an organization’s soft components. Although some researchers propose that the initial step in the digital transformation process should be to establish a digital organizational culture and subsequently develop digital capabilities, we present an alternative approach. It suggests that the establishment of digital leadership should initiate the development of the required digital competencies, which, when combined with digital leadership, will force a transformation of the organizational culture.